Roger Morrice and the Puritan Whigs : the Entring book, 1677-1691 - Goldie, Mark (Boydell Press, 2016)
Mark Goldie's authoritative and highly readable introduction to the political and religious landscape of Britain during the turbulent era of later Stuart rule.